OPTIMASI BIAYA ALTERNATIF PEMILIHAN PONDASI TOWER DI KOTA PEKANBARU - Soewignjo Agus Nugroho; Rian Tri Komara; Ari S. Sibarani (Jurnal APTEK, 2014)
The purpose of this study is to analyze the design and costs required to implement the tower foundation construction and foundation type to vary the diameter and depth of the foundation. It is expected that this study will provide benefits in the selection of the type and design of tower foundations on different types of soil in the city of Pekanbaru so as to provide a reference for implementing the field.The foundation of the tower there are 3 analyzed the foundation of the palm, bored pile foundation and pile foundation. In order to get the optimal type of foundation, each foundation is divided into 3 alternatives. For the palm foundation foundation depth of 2.2 m is restricted, 2.0 m and 1.8 m. Limited bored pile foundation with a diameter of 0.4 m, 0.5 m and 0.6 m. While the pile foundation used a pole with side length 0.2 m, 0.25 m and 0.3 m. Based on the analysis of alternative variations of alternative technical foundation that provides optimum strength with economical cost estimation.